The use of powder metallurgy routes for manufacturing aluminium alloy 6061 and aluminium alloy 6061 Based matrix - sic. Composites - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRAC Powder metallurgy routes have been used to manufacture unreinforced aluminium alloy 6061 (AA6061) and aluminium alloy 6061 based metal matrix composites (MMCs). The materials were composed from elemental aluminium based 6061 powders. The composites were reinforced by isyaic with the average size of 23 gm. The materials were vacuum degassed at 470°C and continuously vacuum sintered at 610°C and 620°C for AA6061 and MMCs, respectively. Samples were cut from the as sintered billets to examine the quality of the materials through a microstructures observation. Residual porosity was found in all materials and the density was 93 - 95% from the theoretical value. A relatively good dispersion of SiC was achieved and the SiC clustering was shown unlikely to occur. The as sintered billets were solution homogenised at 530°C for 1.0 h and directly hot rolled at 500°C and 520°C for AA6061 and MMCs, respectively. The cross sectional reduction was designed 3% - 7%, and to avoid a temperature drop the billets were reheated for each pass. A total reduction of 52% in cross sectional area was achieved for AA6061 after 15 passeS and surface cracks started to appear. However, only a total reduction of 28% can be achieved for MMCs after 5 passes and edge cracks started to. occur. From the microstructures observation showing that the porosity was significantly reduced, the SiC reinforcements were aligned in the rolling direction, and a near theoretical density was achieved The hardness of the as sintered billets was 55 HV20 and 60 HV20 for AA6061 and MMC